(untitled) - Akinyemi, Rowena (Oxford, 1999)
In the Molly Clarkson's fiftieth birthday. She is having a party. She is rich, but she is having a small party - only four people. Four people, however, who all need the same thing: They need her maney. She will not give them the meney, so they are waiting for her to die. And there are other people who are also waiting for her to die. But one person can't wait. And so, on her fiftieth birthday, Molly Clarkson is going to die.
Keywords: English fiction,English literature; 20th century